Effects of odor on emotion, with implications - Kadohisa, Mikiko (Frontiers in Systems Neuroscience, 2013)
The sense of smell is found widely in the animal kingdom. Human and animal studies show that odor perception is modulated by experience and/or physiological state (such as hunger), and that some odors can arouse emotion, and can lead to the recall of emotional memories. Further, odors can influence psychological and physiological states. Individual odorants are mapped via gene-specified receptors to corresponding glomeruli in the olfactory bulb, which directly projects to the piriform cortex and the amygdala without a thalamic relay. The odors to which a glomerulus responds reflect the chemical structure of the odorant. The piriform cortex and the amygdala both project to the orbitofrontal cortex which with the amygdala is involved in emotion and associative learning, and to the entorhinal/hippocampal system which is involved in long-term memory including episodic memory. Evidence that some odors can modulate emotion and cognition is described, and the possible implications for the treatment of psychological problems, for example in reducing the effects of stress, are considered.